2022
DOI: 10.3390/app12042012
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of Hydrocarbon-Polluted Soil: Evaluation of Different Operative Parameters

Abstract: The bioremediation of soils polluted with hydrocarbons demonstrated to be a simple and cheap technique, even if it needs a long time. The current paper shows the application of statistical analysis, based on two factors involved in the biological process at several levels. We focus on the Design of Experiments (DOE) to determine the number and kind of experimental runs, whereas the use of the categorical factors has not been widely exploited up to now. This method is especially useful to analyze factors with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…It was sieved using an industrial mesh for particles smaller than 4,75 mm, according to Cuban standards based on ASTM norms (ASTM International, 2002. For the mixture of texturizers, the best candidates for different treatments were selected, which had been tested in previous stages of the BIOPILA project (Casals et al, 2020;Gutiérrez et al, 2020;Castro et al, 2022c;Castro et al, 2022d). On the one hand, the candidate which reported the lowest TPH concentrations at 240 days, the highest degradation kinetic rate, and the shortest half-life (t 1/2 ) among all the considered treatments was used.…”
Section: Selection Collection and Characterization Of Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was sieved using an industrial mesh for particles smaller than 4,75 mm, according to Cuban standards based on ASTM norms (ASTM International, 2002. For the mixture of texturizers, the best candidates for different treatments were selected, which had been tested in previous stages of the BIOPILA project (Casals et al, 2020;Gutiérrez et al, 2020;Castro et al, 2022c;Castro et al, 2022d). On the one hand, the candidate which reported the lowest TPH concentrations at 240 days, the highest degradation kinetic rate, and the shortest half-life (t 1/2 ) among all the considered treatments was used.…”
Section: Selection Collection and Characterization Of Materialsmentioning
confidence: 99%
“…The BIOPILA project aims to address an innovative and resilient technique to cope with the environmental problem of soil polluted with hydrocarbons in Cuba, specifically with the residues generated by the local industry which remain confined without a solution (Castro et al, 2022a). Previous research carried out within the framework of the aforementioned project has shown, at the bench scale, the relevance of biopile ecotechnology for the degradation of soils polluted with hydrocarbons (Gutiérrez et al, 2021;Castro et al, 2022b, Gutiérrez, et al, 2022Castro et al, 2022c). Significant removal rates were reported for oils and grease concentrations (between 50,05 and 66,08%).…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy to point out that most of the bioremediation studies used low concentrations of crude oil reaching 7% (Hesnawi and Mogadami, 2013 ; Qiao et al, 2013 ; Goudarztalejerdi et al, 2015 ; Siles and Margesin, 2018 ; Castro Rodríguez et al, 2022 ). Vasilyeva et al ( 2020 ) used oil concentrations of 5–15% and reported that bioremediation can be applied on oil concentrations less than 5% only due to toxicity.…”
Section: Introductionmentioning
confidence: 99%